DLC-Si protective coatings for polycarbonates - Damasceno J.C.; Camargo Jr. S.S.; Cremona M. (Materials Research, 2003)
In this work, a-C:H:Si (DLC-Si) films were produced onto crystalline silicon and polycarbonate substrates by the rf-PACVD technique from gaseous mixtures of CH4 + SiH4 and C2H2 + SiH4. The effects of self-bias and gas composition upon mechanical and optical properties of the films were investigated. Micro-hardness, residual stress, surface roughness and refractive index measurements were employed for characterization. By incorporating low concentrations of silicon and by exploring the more favorable conditions for the rf-PACVD deposition technique, highly adherent DLC-Si thin films were produced with reduced internal stresses (lower than 1 GPa), high hardness (around 20 GPa) and high deposition rates (up to 10 µm/h). Results that show the technological viability of this material for application as protective coatings for polycarbonates are also discussed.